Efficacy of inhaled medications in asthma and COPD related to disease severity. (1st December 2016) - Hajian, Bita; De Backer, Jan; Vos, Wim; Aerts, Jelle; Cluckers, Johan; De Backer, Wilfried
ABSTRACT: Introduction : The administration of medication by inhalation has become the most important route in treating airway diseases. The efficacy of this route depends on several factors like correct inhalation techniques, compliance and the size of the particles. The flow properties and internal flow distribution contribute to the deposition pattern. Areas covered : What has been less well studied is the effect of the internal flow distribution. We know from recent studies that using systemic anti-inflammatory compounds that open up the distal airways redistributes flow internally and enhances the deposition of inhaled particles to the active site of bronchoconstriction or airway inflammation. We discuss this in more detail in this paper, and also make reference to the use of functional respiratory imaging (FRI) that allows for the description of this flow pattern starting from chest CT followed by post processing with segmentation software and the application of fluid dynamics. Expert opinion : The method that was previously validated does show the importance of redistribution of flow in the final clinical results that could be obtained with inhaled medication, especially in more severe obstructive airway diseases. Based on these insights and novel diagnostic tools, patients in end stage respiratory failure would benefit from a personalized approach with inhaled medication.